An unusual foreign body tooth brush in esophagus: a case report - K, Shashidhar; Hebbar, Ashwin K.; K., Leena (International Journal of Research in Medical Sciences, 2017)
We report a rare case of accidental toothbrush swallowing by a normal adult which was successfully removed by rigid esophagoscope. A 25 year young man presented to casualty of KIMS, Hubli, with ingestion of toothbrush accidentally half an hour before. Patient’s general physical examination and systemic examination was normal. Oral cavity, oropharynx and indirect laryngoscopic findings were normal. An emergency upper GI Endoscopy was done and foreign body was confirmed to be present at 35 cm from upper incisor teeth. Foreign body was removed by rigid esophagoscope under GA. Otolaryngologist is the most common medical faculty consulted for management of aero digestive foreign bodies. Toothbrush swallowing in normal adults is a rare accident. Most of them are found in esophagus and spontaneous passage is unknown and hence the need for early removal.